Enhancing Students’ Reading Comprehension: The Integration of Reciprocal Teaching and Communicative Language Teaching - Krismayani, Ni Wayan (International Journal of English Education and Linguistics (IJoEEL), 2025)
Reading comprehension is an important skill when studying English, yet many EFL students have difficulty reaching the required proficiency levels. While both Communicative Language Teaching (CLT) and Reciprocal Teaching (RT) are successful when used separately, little research has been done on how they might be used together to improve reading comprehension, especially in EFL university settings. This study explores integrating reciprocal and communicative language teaching strategies on students' reading comprehension. This research utilized classroom action research with pre-tests and post-tests to gather quantitative data and questionnaires to assess students' responses. The findings consistently indicate that integrating Reciprocal Teaching (RT) and Communicative Language Teaching (CLT) significantly enhances students' reading comprehension. The students show positive experiences through tests and questionnaires, including improved text comprehension, increased self-confidence, and a more engaging learning environment. Based on these outcomes, it is recommended that lecturers integrate reciprocal teaching and communicative language teaching to improve reading comprehension skills. The findings show that integrating RT and CLT significantly improves English reading comprehension and usage of these strategies in EFL students. Reading is a crucial English language skill, yet students' comprehension achievement is often below expectations. Keywords: Communicative language teaching, integrating, reading, reciprocal teaching